Periodontal Pathogens Invade Gingiva and Aortic Adventitia and Elicit Inflammasome Activation in αvβ6 Integrin-Deficient Mice - Velsko, Irina M. (Infect Immun, 2015)
The American Heart Association supports an association between periodontal diseases and atherosclerosis but not a causal association. This study explores the use of the integrin β6(−/−) mouse model to study the causality. We investigated the ability of a polymicrobial consortium of Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia, and Fusobacterium nucleatum to colonize the periodontium and induce local and systemic inflammatory responses. Polymicrobially infected Itgβ6(−/−) mice demonstrate greater susceptibility to gingival colonization/infection, with severe gingival inflammation, apical migration of the junctional epithelium, periodontal pocket formation, alveolar bone resorption, osteoclast activation, bacterial invasion of the gingiva, a greater propensity for the bacteria to disseminate hematogenously, and a strong splenic T cell cytokine response. Levels of atherosclerosis risk factors, including serum nitric oxide, oxidized low-density lipoprotein, serum amyloid A, and lipid peroxidation, were significantly altered by polybacterial infection, demonstrating an enhanced potential for atherosclerotic plaque progression. Aortic gene expression revealed significant alterations in specific Toll-like receptor (TLR) and nucleotide-binding domain- and leucine-rich-repeat-containing receptor (NLR) pathway genes in response to periodontal bacterial infection. Histomorphometry of the aorta demonstrated larger atherosclerotic plaques in Itgβ6(−/−) mice than in wild-type (WT) mice but no significant difference in atherosclerotic plaque size between mice with polybacterial infection and mice with sham infection. Fluorescence in situ hybridization demonstrated active invasion of the aortic adventitial layer by P. gingivalis. Our observations suggest that polybacterial infection elicits distinct aortic TLR and inflammasome signaling and significantly increases local aortic oxidative stress. These results are the first to demonstrate the mechanism of the host aortic inflammatory response induced by polymicrobial infection with well-characterized periodontal pathogens.